Oral carcinogenesis and non-invasive biomarkers for the diagnosis of oral squamous cell carcinoma - Khan, Samreen; Alamgir, Muhammad Mohiuddin (Journal of the Pakistan Medical Association, 2024)
Oral squamous cell carcinoma (OSCC) is the most prevalent cancer in Pakistani population because of consumption of different tobacco-containing products whether smoked or chewed. These patients commonly report at a late stage of the disease. The patient’s survival only depends upon early-stage diagnosis. Literature has reported that there is an increased tendency of transformation of oral potentially malignant disorder (OPMD) into OSCC. Biopsy is the gold standard measure for diagnosis but for OPMD cases biopsy was not recommended and most of the times the patients were also not willing to have a biopsy done. So, along with the biopsy there is a need for non-invasive protein biomarker that might aid in the early detection of oral cancer as well as highlight the high-risk individuals. ---Continue